Enhancing learning outcomes through course redesign using self-assessment and inquiry models - Martinez, Fredy; Hernández, César; Giral, Diego (Institute of Advanced Engineering and Science, 2025)
This study addresses the challenge of enhancing learning outcomes in propaedeutic education by redesigning an undergraduate deep learning course. To achieve this, the self-assessment and quality model (SQM) was combined with the community of inquiry (CoI) framework, which emphasizes cognitive, social, and teaching presence in online education. The redesigned course aligns with the guidelines of the Colombian Ministry of National Education and incorporates continuous feedback from students. Initial implementation led to improved student performance but revealed gaps in perceived learning experiences. Iterative adjustments were made to the course design based on CoI survey results, particularly focusing on increasing teacher involvement. The findings demonstrate that integrating SQM with a responsive, design-based approach can significantly improve learning outcomes and student satisfaction. This study highlights the importance of dynamic course design in higher education and offers a replicable model for other institutions.